Aeitiological evaluation of Anaemia in one hundred patient admitted in a Tertiary Hospital (Journal of Dhaka National Medical College & Hospital, 2016)
Anaemia is a condition where there is a lower than normal number of red blood cells (RBCs) in the blood, usually measured by decrease in the amount of hemoglobin (Hb)1. Anemia is a very common problem encountered in our clinical practice. So, knowledge about the aetiological pattern of anaemia of patients admitted in tertiary hospitals will help the clinician in planning investigations for early diagnosis and effective management of the patients. A cross sectional study was carried out over a period of 12 months in total 100 patients with severe anaemia having Hb level below 6 gm/dl admitted in tertiary care hospital. Result of this study was Anaemia due to marrow replacement by haematological malignancies like leukaemia, lymphoma,multiple myeloma, myelofibrosis etc. were found to have highest incidence in this study (42%), Anaemia of chronic disorder 23%, Aplastic anaemia 12%, Haemolytic anaemia 9%, Iron deficiency anaemia 7%, Megaloblastic anaemia 4%, Anaemia due to acute blood loss 3%. It is concluded that in this study Heamatological malignancy appeared to most common cause of anaemia. Anaemia associated with chronic disorders were found to be the second most common causes of anaemia. Aplastic anaemia was the third most common in Tertiary HospitalJ. Dhaka National Med. Coll. Hos. 2016; 22 (01): 24-26